2012
DOI: 10.1258/ijsa.2011.011200
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with anxiety disorders among HIV-positive attendees of an HIV clinic in Lagos, Nigeria

Abstract: Anxiety disorders (ADs) occurring in people living with HIV/AIDS (PLWHA) are often poorly identified in spite of the untold consequences that may result if not diagnosed and treated promptly. This study aimed to describe factors associated with ADs among PLWHA. Three hundred participants were administered sociodemographic/clinical profile questionnaires, and diagnoses of ADs were made using Schedule for Clinical Assessment in Neuropsychiatry (SCAN) based on International Classification of Diseases, 10th editio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…30 39 In one of them, 39 PLWH50 + on ART presented with the same proportion of anxiety symptoms with HIV uninfected older adults at 3%. In the other study, 30 the prevalence of anxiety disorders among PLWH50 + on ART was 21% compared with 22% in HIV infected young adults (18-50 years).…”
Section: Prevalence Of Depression and Anxietymentioning
confidence: 74%
“…30 39 In one of them, 39 PLWH50 + on ART presented with the same proportion of anxiety symptoms with HIV uninfected older adults at 3%. In the other study, 30 the prevalence of anxiety disorders among PLWH50 + on ART was 21% compared with 22% in HIV infected young adults (18-50 years).…”
Section: Prevalence Of Depression and Anxietymentioning
confidence: 74%
“…Psychiatric disorders occur in up to 50% of individuals with HIV (1215). The most commonly reported of these are depression, anxiety disorders and substance use disorders (14,1618). The role of these disorders in reducing quality of life and accelerating the progression of HIV disease(1921) is mediated through a number of factors, including an increased likelihood of suboptimal treatment adherence (2224).…”
Section: Introductionmentioning
confidence: 99%
“…12–15 The most commonly reported of these are depression, anxiety disorders and substance use disorders. 14,1618 These disorders act to reduce quality of life and accelerate the progression of HIV disease 1921 through a number of mechanisms, including an increased likelihood of suboptimal treatment adherence. 2224 Much research has demonstrated associations between psychiatric disorders and ART adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Other than that, 89% of patients with HIV who were diagnosed to have GAD were single. Single patients had increased odds of having anxiety by 3.6 times compared to the patients who were married (Ngocho et al, 2019) and similar studies showed that being unmarried had 2-times higher risk to develop anxiety (p=0.002) (Olagunju et al, 2012). HIVinfection is a chronic disease which needs endless support as they face various social challenges.…”
Section: Discussionmentioning
confidence: 97%